2017
DOI: 10.1111/tct.12691
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ views of clinical environments

Abstract: UCEEM appears to be a useful tool for evaluating medical student perceptions of CLEs. Theoretically robust, UCEEM is straightforward to administer and to score. It has the potential to be used by time-pressured educators to collect baseline and comparative data for evaluation and improvement purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
2
15
0
3
Order By: Relevance
“…Robert et al (2017) reported that obstetrics and gynecology wards obtained the lowest scores in terms of the clinical education environment. 41 Consistent with Abbasi et al, there was no significant difference in students' viewpoints based on marital status. 20 There was a significant relationship between the students' viewpoints on the internship ward and the days of attendance in the wards.…”
Section: Discussionsupporting
confidence: 82%
“…Robert et al (2017) reported that obstetrics and gynecology wards obtained the lowest scores in terms of the clinical education environment. 41 Consistent with Abbasi et al, there was no significant difference in students' viewpoints based on marital status. 20 There was a significant relationship between the students' viewpoints on the internship ward and the days of attendance in the wards.…”
Section: Discussionsupporting
confidence: 82%
“…The clinical learning environment affects learning, learners' well-being, and satisfaction [8,9], thereby affecting learning ability, learning attitude, and career development [10]. Considering the significance of clinical practice in nursing and medical education, monitoring and improving the clinical learning environment is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…However, the measurement tools had limitations in measuring some critical educational phenomena since many of them lack a theoretical basis, consider the clinical learning environment as a mere educational arena, and fail to acknowledge that it is a workplace as well [9,15]. They mainly measured either learning conditions in clinical placement or learning environments and supervision [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A s fourth-year medical students, we read with interest the study by Roberts et al on medical students' views of clinical learning environments (CLEs). 1 The authors assessed the quality of four CLEs at one British medical school using the four-factor Undergraduate Clinical Education Environment Measure.…”
mentioning
confidence: 99%
“…We note that emergency medicine was highly ranked in this domain. 1 In our experience, this particular team involves us effectively, allocating patients for us to clerk and prompting us to suggest management plans. Perhaps this is because encouraging students to carry out such tasks helps to share the workload in the hectic environment of the emergency room.…”
mentioning
confidence: 99%